Use of Aldosterone Antagonists for Treatment of Uncontrolled Resistant Hypertension - Dudenbostel, Tanja (Am J Hypertens, 2017)
BACKGROUND: Multiple studies indicate that primary aldosteronism (PA) is common in patients with resistant hypertension, with an estimated prevalence of approximately 20%. Additional studies suggest that beyond this 20% of patients with classical PA, there is a larger proportion of patients with lesser degrees of hyperaldosteronism which contributes even more broadly to antihypertensive treatment resistance. Given these observations, it is intuitive that use of aldosterone antagonists will provide antihypertensive benefit in patients with resistant hypertension and evidence of aldosterone excess. Intriguingly, however, are clinical findings demonstrating substantive benefit of aldosterone antagonists in patients with resistant hypertension, but without demonstrative evidence of hyperaldosteronism, that is, with seemingly normal or even low aldosterone levels. CONCLUSION: Spironolactone is clearly established as the most effective fourth agent for treatment of uncontrolled resistant hypertension. Emerging observations suggest a further role of spironolactone for counteracting the effects of diet high in sodium, particularly in obese, hypertensive patients.